ARTHROSCOPIC TREATMENT OF SHOULDER IMPINGEMENT SYNDROME IN ONE-DAY HOSPITAL - Martin Mikek (Zdravniški Vestnik, 2004)
Background. Arthroscopic subacromial decompression is the method of choice in operative treatment of subacromial rotator cuff impingement. In General Hospital Novo mesto the procedure is performed on a basis of one-day surgery. Methods. We present a prospective analysis of results of operative treatment of shoulder impingement in 36 patients. In all patients functional shoulder scores according to Constant, SST and UCLA were recorded before the operative procedure and again at least three months after the index procedure. Results. According to acromial morphology in the observed group there were three patients with type I acromion (8%), 22 patients had type II acromion (61%) and 11 had acromion type III (31%). The average Constant score improved from 21 (SD ± 15) before the operation to 78 (SD ± 12) after the operation and average SST score improved from 4,7 (SD ± 2) to 7,5 (SD ± 1.4) and average UCLA score from 11 (SD ± 3) to 26 (SD ± 3). Conclusions. We conclude that arthroscopic subacromial decompression in properly selected patients enables attainment of good or excellent results in over 90% of patients. Because of minimal invasivness the procedure can be safely performed as one-day surgery.